An empirical investigation of the incidence of negative psychological symptoms among Chinese international students at an Australian university. (30th October 2015) - Redfern, Kylie
Abstract: Objective: To examine comparative levels of depression, anxiety, and stress among a sample of Chinese international students and local Australian students studying at a major Australian university, and to elicit the main sources of symptoms in these groups. Method: The study used the Depression, Anxiety and Stress Scale (DASS‐42) to measure scores on each of the subscales in a sample of 201 undergraduate students. Differences between the local students, Australian students, and Chinese international students are reported. Qualitative data are analysed to determine the main sources of students' psychological symptoms. Results: Australian students' stress levels fell between the 'mild' to 'moderate' categories, while Chinese students' stress levels fell within the 'moderate' category. Anxiety levels were between 'normal' and 'mild' for Australian students, and between 'moderate' and 'severe' for Chinese students. Depression levels fell in the upper range of 'normal' for both groups. Chinese students' levels of both stress and anxiety were significantly higher than for local students. Academic, life balance, and family factors were found to be the main sources of stress for Chinese students. Conclusions: Chinese international students experience significantly higher levels of anxiety and stress than their Australian counterparts, and the causes of these appear to be culture‐specific. Universities have a duty of care to address the phenomena of psychological morbidity among Chinese international students. Approaches to psychological support services, including counselling and academic support, should be culturally specific and must be reinforced constantly during the semester as stress and anxiety accumulate.